Analysis of the Impact of the General Election on Consumption Levels, Investment, Inflation and Stock Price Index to Maintain Economic Stability and Anticipate the Impact - Hakim, Luqman (PT FORMOSA CENDEKIA GLOBAL, 2024)
The 2024 election is a critical point in determining future Indonesian government policies, especially in attracting foreign investment. Investors often adopt a wait-and-see attitude during election periods. Analysis of quarterly and annual data regarding the impact of elections on macroeconomic indicators is crucial for making economic policies. During the election, there was a significant increase in consumption, investment, and money supply, but only the money supply was significantly affected in the quarter before and during the election which was driven by large campaign spending. Investment tends to increase before political uncertainty increases, while consumption rises significantly only during elections, driven by campaign activities. Post-election, increased political stability restored investor confidence and boosted the composite stock price index (IHSG).